Optimization of sensory properties of ultrasound-treated strawberry vinegar - Melikenur Türkol; Seydi Yıkmış; Şennur Ganimet; Göktuğ Egemen Gezer; Gholamreza Abdi; Shahzad Hussain; Rana Muhammad Aadil (Ultrasonics Sonochemistry, 2024)
Vinegar is renowned for its benefits to human health due to the presence of antioxidants and bioactive components. Firstly, this study optimized the production conditions of ultrasound-treated strawberry vinegar (UT-SV), known for its high consumer appeal. The sensory properties of UT-SV were optimized by response surface methodology (RSM) to create the most appreciated strawberry vinegar. Secondly, various quality parameters of conventional strawberry vinegar (C-SV), UT-SV, and thermally pasteurized strawberry vinegar (P-SV) samples were compared. RSM was employed to craft the best strawberry vinegar based on consumers ratings of UT-SV. Sensory characteristics, bioactive values, phenolic contents, and organic acid contents of C-SV, UT-SV, and P-SV samples were assessed. Through optimization, the ultrasound parameters of the independent variables were determined as 5.3 min and 65.5 % amplitude. The RSM modeling levels exhibited high agreement with pungent sensation at 98.06 %, aromatic intensity at 98.98 %, gustatory impression at 99.17 %, and general appreciation at 99.26 %, respectively. Bioactive components in UT-SV samples increased after ultrasound treatment compared to C-SV and P-SV samples. Additionally, the amount of malic acid, lactic acid, and oxalic acid increased after ultrasound treatment compared to C-SV samples. Ultimately, UT-SV with high organoleptic properties was achieved. The ultrasound treatment positively impacted the bioactive values, phenolic and organic acid content, leading to the development of a new and healthy product.